Adhesive sheet
The adhesive sheet with a specific Sp value and high affinity with the sealing resin, combined with thermally expandable microspheres, addresses the issue of surface defects post-peeling in semiconductor chip resin sealing, ensuring a smooth and adhered surface.
Patent Information
- Application Number
- JP2022575070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-15
- Filing Date
- 2021-09-16
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-09-16
AI Technical Summary
Conventional adhesive sheets used in the resin sealing process for semiconductor chips result in uneven surfaces after peeling, leading to appearance defects in the sealing resin.
A pressure-sensitive adhesive sheet with a specific Sp value range (19.5 to 25 J/cm3/2) and high affinity with the sealing resin, along with optional second adhesive layers containing thermally expandable microspheres, to ensure smooth peeling and prevent surface defects.
The adhesive sheet effectively prevents flow marks and surface unevenness, maintaining a smooth resin surface and improving adhesion to semiconductor chips during and after the peeling process.
Smart Images

Figure 0007600272000002 
Figure 0007600272000003 
Figure 0007600272000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]
[0002] In recent years, in the manufacture of semiconductor parts including semiconductor chips, the semiconductor chips are sometimes resin-sealed to prevent the semiconductor chips from being scratched and to expand the metal wiring. In the resin sealing process, the semiconductor chips are sometimes resin-sealed on an adhesive sheet from the viewpoint of workability. For example, in order to prevent the semiconductor chips from moving, multiple semiconductor chips are placed on an adhesive sheet as a predetermined temporary fixing material, and the semiconductor chips are resin-sealed together on the adhesive sheet. Then, in a predetermined post-process, the adhesive sheet is peeled off from the resin that has sealed the semiconductor chips.
[0003] In the above-mentioned process, when a conventional adhesive sheet is used, there is a problem that after the adhesive sheet is peeled off, unevenness in appearance occurs on the surface of the sealing resin that was in contact with the adhesive sheet. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-308116 A [Patent Document 2] JP 2001-313350 A [Patent Document 3] JP 2018-193563 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned conventional problems, and an object of the present invention is to provide an adhesive sheet that can be used as a temporary fixing material when resin sealing a semiconductor chip, and that can prevent poor appearance of the sealing resin after the adhesive sheet is peeled off. [Means for solving the problem]
[0006] The pressure-sensitive adhesive sheet of the present invention comprises a substrate and a pressure-sensitive adhesive layer disposed on at least one side of the substrate, the pressure-sensitive adhesive layer containing a pressure-sensitive adhesive, and the pressure-sensitive adhesive has an Sp value of 19.5 (J / cm 3 ) 1 / 2 ~25(J / cm 3 ) 1 / 2 The base polymer comprises In one embodiment, the pressure-sensitive adhesive sheet comprises the substrate, the pressure-sensitive adhesive layer disposed on one side of the substrate, and a second pressure-sensitive adhesive layer disposed on the side of the substrate opposite the pressure-sensitive adhesive layer. In one embodiment, the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive. In one embodiment, the acrylic pressure-sensitive adhesive comprises a base polymer having an alkyl ester having 6 or less carbon atoms as a side chain, and the content of structural units having an alkyl ester having 6 or less carbon atoms as the side chain is 50% by weight or more relative to all structural units constituting the acrylic polymer. In one embodiment, the pressure-sensitive adhesive layer has a contact angle of 47° or less with 4-tert-butylphenyl glycidyl ether. In one embodiment, the adhesive strength of the epoxy resin at 23° C. when the epoxy resin is cured on the pressure-sensitive adhesive layer is preferably 8 N / 20 mm or more. In one embodiment, the pressure-sensitive adhesive layer has a shear adhesive strength of 400 g or more at 150° C. when attached to a silicon chip. Effect of the Invention
[0007] According to the present invention, it is possible to provide an adhesive sheet that can be used as a temporary fixing material when resin sealing a semiconductor chip, and that can prevent poor appearance of the sealing resin after the adhesive sheet is peeled off. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to another embodiment of the present invention. [Diagram 3] 1A to 1C are SEM photographs showing the results of "cross-sectional observation of sealing resin" in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] A. Overview of adhesive sheets 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. The pressure-sensitive adhesive sheet 100 comprises a substrate 10 and a pressure-sensitive adhesive layer (first pressure-sensitive adhesive layer) 20 disposed on at least one side of the substrate 10.
[0010] The pressure-sensitive adhesive sheet of the present invention can be suitably used as a temporary fixing material when a semiconductor chip is resin-sealed. More specifically, the pressure-sensitive adhesive sheet of the present invention can be used as a temporary fixing material for a semiconductor chip when the semiconductor chip is arranged on the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet, the semiconductor chip is covered with a resin (usually an epoxy resin), and the sealing resin is cured to resin-seal the semiconductor chip. After the semiconductor chip is resin-sealed, the pressure-sensitive adhesive sheet can be peeled off from the structure composed of the sealing resin and the semiconductor chip during a predetermined post-process (for example, back grinding of the sealing resin, pattern formation, bump formation, chipping (cutting)).
[0011] The pressure-sensitive adhesive layer contains a pressure-sensitive adhesive having an Sp value of 19.5 (J / cm 3 ) 1 / 2 ~25(J / cm 3 ) 1 / 2The base polymer includes a base polymer having an Sp value in this range. In the present invention, by using a base polymer having an Sp value in this range, a pressure-sensitive adhesive layer having high affinity with the encapsulating resin can be formed. When a pressure-sensitive adhesive sheet having such a pressure-sensitive adhesive layer is attached to the encapsulating resin and subjected to a resin encapsulation process, a mixed layer containing a pressure-sensitive adhesive layer component and a encapsulating resin component is preferably formed between the encapsulating resin and the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet by heating and pressing during the process. As a result, after the operation of peeling the pressure-sensitive adhesive sheet from the encapsulating resin, the appearance defect (flow mark) of the surface of the encapsulating resin to which the pressure-sensitive adhesive sheet was attached is prevented. In one embodiment, when the operation of peeling the pressure-sensitive adhesive sheet is performed, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet peels off from the substrate and remains on the encapsulating resin, partly due to the formation of the mixed layer. As a result, the effect of preventing the flow mark is remarkable. In addition, the adhesion of the wiring formed in the structure including the semiconductor chip can be improved. Furthermore, after peeling, the step between the surface of the encapsulating resin and the semiconductor chip can be reduced.
[0012] Conventionally, flow marks have been considered to be caused by variations in thickness of a mixed layer formed by mixing low molecular weight components of the encapsulating resin with adhesive components of the adhesive layer, and development of an adhesive sheet having an adhesive layer with low affinity to the encapsulating resin (for example, an adhesive layer containing an adhesive with a low Sp value) has been considered as an adhesive sheet for temporary fixing of resin encapsulation. On the other hand, the present invention is based on a concept completely different from that of conventional adhesive sheets, that is, is characterized in that flow marks can be prevented by forming an adhesive layer with high affinity to the encapsulating resin.
[0013] 2 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to another embodiment of the present invention. The pressure-sensitive adhesive sheet 200 further comprises a second pressure-sensitive adhesive layer 30 on the side of the substrate 10 opposite the pressure-sensitive adhesive layer 20. That is, the pressure-sensitive adhesive sheet 200 comprises the pressure-sensitive adhesive layer 20, the substrate 10, and the second pressure-sensitive adhesive layer 30, in this order. By providing the second pressure-sensitive adhesive layer 30, when performing resin sealing on a pedestal, the second pressure-sensitive adhesive layer 30 side can be attached to the pedestal, allowing the pressure-sensitive adhesive sheet 200 to be positioned with good fixation.
[0014] In one embodiment, the second pressure-sensitive adhesive layer contains heat-expandable microspheres. The heat-expandable microspheres can expand at a predetermined temperature. When the pressure-sensitive adhesive layer containing such heat-expandable microspheres is heated to a predetermined temperature or higher, the heat-expandable microspheres expand, causing unevenness on the adhesive surface (i.e., the surface of the second pressure-sensitive adhesive layer), and the adhesive strength is reduced or lost. By forming a second pressure-sensitive adhesive layer containing heat-expandable microspheres, the adhesive strength required for fixing the pressure-sensitive adhesive sheet (e.g., fixing it to a base) is exhibited, and when the pressure-sensitive adhesive sheet is peeled off (e.g., peeled off from the base), the adhesive strength is reduced or lost by heating, and good peelability is exhibited.
[0015] The adhesive sheet of the present invention has an adhesive strength at 23°C when the adhesive layer is attached to polyethylene terephthalate of preferably 0.05N / 20mm to 1N / 20mm, more preferably 0.1N / 20mm to 10N / 20mm, even more preferably 0.1N / 20mm to 5N / 20mm, particularly preferably 0.2N / 20mm to 2N / 20mm, and most preferably 0.2N / 20mm to 1N / 20mm. Within such ranges, an adhesive sheet can be obtained that can favorably fix an adherend (e.g., a semiconductor chip) and leaves little adhesive residue when peeled off. In this specification, "adhesive strength at 23°C when the adhesive layer is attached to polyethylene terephthalate" refers to the adhesive strength measured by laminating the adhesive layer of an adhesive sheet (width 20 mm × length 100 mm) to a polyethylene terephthalate film (thickness 25 μm) (lamination conditions: one round trip with a 2 kg roller), leaving it at an environmental temperature of 23°C for 30 minutes, and then subjecting the sample to a tensile test (peel speed: 300 mm / min, peel angle 180°).
[0016] The adhesive sheet of the present invention has an adhesive strength at 23°C to the epoxy resin when the epoxy resin is cured on the adhesive layer of preferably 8N / 20mm or more, more preferably 8N / 20mm to 20N / 20mm, and even more preferably 8N / 20mm to 15 / 20mm. The "adhesive strength at 23°C to the epoxy resin when the epoxy resin is cured on the adhesive layer" is an index showing the adhesion between the adhesive sheet and the sealing resin. If the adhesive strength is within the above range, an adhesive sheet suitable as a temporary fixing material when resin sealing a semiconductor chip can be obtained. In this specification, the "adhesive strength at 23°C to the epoxy resin when the epoxy resin is cured on the adhesive layer" means a peeling force when peeling the epoxy resin from the adhesive layer for a sample obtained by applying an epoxy resin (for example, product name "G730" manufactured by Sumitomo Bakelite Co., Ltd.) before curing on the adhesive layer and then curing the epoxy resin. The adhesive strength (peeling strength) is measured by subjecting the above sample having a width of 20 mm and a length of 100 mm to a tensile test (peeling speed: 300 mm / min, peeling angle: 180°).
[0017] The adhesive sheet of the present invention has a shear adhesive strength at 150°C when the adhesive layer is attached to a silicon chip of preferably 400g or more, more preferably 400g to 2000g, and even more preferably 700g to 1500g. Within such a range, the adhesive has a high cohesive strength, and has a preferable adhesive strength even at high temperatures (for example, a heating step for curing the encapsulating resin), and can prevent the positional displacement of an adherend (for example, a semiconductor chip) placed on the adhesive sheet. In addition, it can prevent the formation of a gap (a gap between the adhesive sheet / encapsulating resin) through which the encapsulating resin can enter. The shear adhesive strength can be measured by reading the maximum breaking load from a load-displacement curve obtained by attaching a silicon chip (size: 5mm x 5mm mirror surface) vertically to the adhesive layer so that the chip corner does not come into contact with the adhesive layer, heating at 130°C for 30 minutes to make the silicon chip adhere to the adhesive surface, and then applying an external force in a horizontal direction to the chip at a shear rate of 500μm / sec in an environment of 150°C.
[0018] The thickness of the pressure-sensitive adhesive sheet of the present invention is preferably 3 μm to 300 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 150 μm.
[0019] B.Adhesive layer The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 300 μm, more preferably 2 μm to 300 μm, even more preferably 2 μm to 200 μm, even more preferably 3 μm to 100 μm, even more preferably 4 μm to 80 μm, and particularly preferably 5 μm to 50 μm. Within such a range, a pressure-sensitive adhesive layer having a flat surface can be formed, and a pressure-sensitive adhesive sheet that is less likely to produce flow marks can be obtained.
[0020] The contact angle of the pressure-sensitive adhesive layer to 4-tert-butylphenyl glycidyl ether is preferably 47° or less, more preferably 25° to 47°, and even more preferably 28° to 45°. Within this range, a pressure-sensitive adhesive layer having high affinity with the sealing resin can be formed.
[0021] The elastic modulus of the pressure-sensitive adhesive layer at 25°C measured by nanoindentation is preferably less than 100 MPa, more preferably 0.1 MPa to 50 MPa, and even more preferably 0.1 MPa to 10 MPa. Within such a range, an adhesive sheet having an appropriate adhesive strength can be obtained. The elastic modulus measured by nanoindentation refers to an elastic modulus obtained by continuously measuring the load applied to the indenter and the indentation depth during loading and unloading when the indenter is pressed into the sample, and then obtaining a load-indentation depth curve. In this specification, the elastic modulus measured by nanoindentation refers to an elastic modulus measured as described above under the measurement conditions of load: 1 mN, loading / unloading rate: 0.1 mN / s, and holding time: 1 s.
[0022] The tensile modulus of the pressure-sensitive adhesive layer at 25° C. is preferably less than 100 MPa, more preferably 0.1 MPa to 50 MPa, and even more preferably 0.1 MPa to 10 MPa. Within this range, a pressure-sensitive adhesive sheet having appropriate adhesive strength can be obtained. The tensile modulus can be measured in accordance with JIS K 7161:2008.
[0023] The probe tack value of the pressure-sensitive adhesive layer is preferably 50 g / 5 mmφ or more, more preferably 75 g / 5 mmφ or more, and even more preferably 100 g / 5 mmφ or more. Within such a range, it is possible to prevent the positional deviation of the adherend (e.g., semiconductor chip) placed on the pressure-sensitive adhesive sheet. The measurement conditions for the probe tack value are probe processing speed: 30 mm / min, test speed: 30 mm / min, contact load: 100 gf, contact retention time: 1 second, and probe area: 5 mmφ SUS.
[0024] <Adhesive> As the adhesive constituting the adhesive layer, any suitable adhesive can be used as long as the effect of the present invention can be obtained. Examples of the adhesive include acrylic adhesives, rubber adhesives, silicone adhesives, etc. Among them, acrylic adhesives can be preferably used. In addition, active energy ray curable adhesives may be used as the adhesive. The adhesive includes a base polymer having an sp value in the above range. The base polymer means a polymer that can be a factor in the development of adhesiveness of the adhesive.
[0025] As mentioned above, the Sp value of the base polymer is 19.5(J / cm 3 ) 1 / 2 ~25(J / cm 3 ) 1 / 2 The Sp value of the base polymer is preferably 20 (J / cm 3 ) 1 / 2 ~24(J / cm 3 ) 1 / 2 and more preferably 20.5 (J / cm 3 ) 1 / 2 ~23.5(J / cm3 ) 1 / 2 Within such a range, the above-mentioned effects of the present invention become remarkable. The Sp value of the base polymer can be calculated by the Fedors method (Hideki Yamamoto, "sp Value: Basics, Applications and Calculation Methods", Johokki Publishing Co., Ltd., published on April 3, 2006, pp. 66-67). Specifically, the sp value is calculated by the evaporation energy Δe (cal) at 25°C of each atom or atomic group forming the polymer, and the molar volume ΔV (cm) at 25°C of each atom or atomic group forming the polymer. 3 ) is calculated using the following formula: Sp value = (ΣΔe / ΣΔv) 1 / 2 When the polymer is a copolymer, the SP value is calculated by calculating the SP value of each homopolymer of each structural unit constituting the copolymer, and then multiplying each of these SP values by the molar fraction of each structural unit and adding up the results.
[0026] (Acrylic adhesive) Examples of the acrylic adhesive include acrylic adhesives having an acrylic polymer (homopolymer or copolymer) as a base polymer, which uses one or more types of (meth)acrylic acid alkyl esters as a monomer component.
[0027] Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and ) C1-20 alkyl (meth)acrylate esters such as nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, preferred are alkyl (meth)acrylate esters having a linear or branched alkyl group having 1 to 16 carbon atoms (more preferably 1 to 12, and particularly preferably 1 to 6).
[0028] The acrylic polymer preferably has an alkyl ester having 6 or less carbon atoms as a side chain, more preferably has an alkyl ester having 4 or less carbon atoms, and even more preferably has an alkyl ester having 2 or less carbon atoms. By using an acrylic polymer having a short side chain, a pressure-sensitive adhesive layer having high affinity with sealing materials can be formed. In the acrylic polymer, the content of the structural unit having an alkyl ester having 6 or less carbon atoms as a side chain (preferably 4 or less, more preferably 2 or less) is preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 60% by weight to 100% by weight, particularly preferably 60% by weight to 90% by weight, and most preferably 60% by weight to 80% by weight, based on the total structural units constituting the acrylic polymer. Within such a range, a pressure-sensitive adhesive layer having high affinity with sealing materials can be formed.
[0029] The acrylic pressure-sensitive adhesive may contain multiple types of acrylic polymers, and the content of the acrylic polymer having an alkyl ester with 6 or less carbon atoms in its side chain (preferably 4 or less, more preferably 2 or less) is preferably 30 to 100 parts by weight, more preferably 70 to 100 parts by weight, and even more preferably 90 to 100 parts by weight, relative to 100 parts by weight of the total acrylic polymers. In one embodiment, the content of the acrylic polymer having an alkyl ester with 6 or less carbon atoms in its side chain is 100 parts by weight, relative to 100 parts by weight of the total acrylic polymers.
[0030] The acrylic polymer may contain units corresponding to other monomer components copolymerizable with the alkyl (meth)acrylate, if necessary, for the purpose of modifying properties such as cohesive strength, heat resistance, and crosslinkability. Examples of such monomer components include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itanoic anhydride; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; (N-substituted) amide monomers such as N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide;succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and methoxyethyl (meth)acrylate. glycol-based acrylic ester monomers such as ethylene glycol and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers having a heterocycle, a halogen atom, a silicon atom, or the like, such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin-based monomers such as isoprene, butadiene, and isobutylene;Examples of the monomer component include vinyl ether monomers such as vinyl ether. These monomer components may be used alone or in combination of two or more. Among the above, more preferred are carboxyl group-containing monomers (particularly preferably acrylic acid) or hydroxyl group-containing monomers (particularly preferably hydroxyethyl (meth)acrylate). The content of the structural unit derived from the carboxyl group-containing monomer is preferably 40% by weight or less, more preferably 0.1% by weight to 10% by weight, even more preferably 0.5% by weight to 5% by weight, and particularly preferably 1% by weight to 4% by weight, based on the total structural units constituting the acrylic polymer. The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.09% by weight to 40% by weight, more preferably 0.1% by weight to 20% by weight, even more preferably 0.5% by weight to 10% by weight, and particularly preferably 1% by weight to 7% by weight, based on the total structural units constituting the acrylic polymer.
[0031] The acrylic adhesive may contain any suitable additives as necessary, such as crosslinkers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.
[0032] Examples of the crosslinking agent contained in the acrylic adhesive include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred.
[0033] Specific examples of the isocyanate-based crosslinking agent contained in the acrylic pressure-sensitive adhesive include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). The content of the isocyanate-based crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the base polymer.
[0034] Examples of the epoxy crosslinking agent contained in the acrylic adhesive include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1500NP"), ), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 70P"), polyethylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol E-400"), polypropylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol P-200"), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, product name "Denacol" Examples of the epoxy crosslinking agent include glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-611"), glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-314"), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-512"), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the base polymer.
[0035] The tackifier contained in the acrylic pressure-sensitive adhesive may be any appropriate tackifier, such as a tackifier resin. Specific examples of the tackifier resin include rosin-based tackifier resins (e.g., unmodified rosin, modified rosin, rosin phenol-based resins, rosin ester-based resins, etc.), terpene-based tackifier resins (e.g., terpene-based resins, terpene phenol-based resins, styrene-modified terpene-based resins, aromatic modified terpene-based resins, hydrogenated terpene-based resins), hydrocarbon-based tackifier resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene-based resins, xylene-based resins, etc.), aliphatic and aromatic petroleum resins, aliphatic and alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone-based resins, coumarone-indene resins, etc.), phenol-based tackifier resins (e.g., alkylphenol-based resins, xylene formaldehyde-based resins, resols, novolacs, etc.), ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, elastomer-based tackifier resins, etc. Among them, rosin-based tackifier resins, terpene-based tackifier resins, or hydrocarbon-based tackifier resins (such as styrene-based resins) are preferred. The tackifiers may be used alone or in combination of two or more. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, based on 100 parts by weight of the base polymer.
[0036] Preferably, a resin having a high softening point or glass transition temperature (Tg) is used as the tackifier resin. By using a resin having a high softening point or glass transition temperature (Tg), a pressure-sensitive adhesive layer that can exhibit high adhesion can be formed even in a high-temperature environment (for example, a high-temperature environment in processing such as when sealing a semiconductor chip). The softening point of the tackifier is preferably 100°C to 180°C, more preferably 110°C to 180°C, and even more preferably 120°C to 180°C. The glass transition temperature (Tg) of the tackifier is preferably 100°C to 180°C, more preferably 110°C to 180°C, and even more preferably 120°C to 180°C.
[0037] The acrylic adhesive may further contain a reaction aid. By adding the reaction aid, it is expected that the effect of preventing adhesive residue due to cohesive failure of the adhesive when peeling off the adhesive sheet after resin sealing can be further improved. When an isocyanate-based crosslinking agent is used, for example, a tin-based organic compound, a titanium-based organic compound, an iron-based organic compound, an amine (TEDA, etc.)-based organic compound, etc. are used as the reaction aid. Specific examples of tin-based organic compounds include "OL-1" manufactured by Tokyo Fine Chemical Co., Ltd. and "Tetraethylenediamine" manufactured by Tosoh Corporation. When an epoxy-based crosslinking agent is used, for example, imidazoles and phosphorus-based organic compounds are used. The content ratio of the reaction aid is preferably 0.001 to 0.5 parts by weight, more preferably 0.005 to 0.1 parts by weight, and even more preferably 0.01 to 0.07 parts by weight, relative to 100 parts by weight of the base polymer.
[0038] (Rubber adhesive) As the rubber-based adhesive, any suitable adhesive can be used as long as the effect of the present invention can be obtained. As the rubber-based adhesive, for example, natural rubber; polyisoprene rubber, butadiene rubber, styrene-butadiene (SB) rubber, styrene-isoprene (SI) rubber, styrene-isoprene-styrene block copolymer (SIS) rubber, styrene-butadiene-styrene block copolymer (SBS) rubber, styrene-ethylene-butylene-styrene block copolymer (SEBS) rubber, styrene-ethylene-propylene-styrene block copolymer (SEPS) rubber, styrene-ethylene-propylene block copolymer (SEP) rubber, reclaimed rubber, butyl rubber, polyisobutylene rubber, or synthetic rubber such as modified products thereof; and the like are preferably used as the base polymer of the rubber-based adhesive. These base polymers (rubbers) have a low sp value, and by using the base polymer, an adhesive layer with low affinity to the sealing material can be formed.
[0039] As the base polymer constituting the rubber-based pressure-sensitive adhesive, polyisobutylene rubber, polyisoprene rubber, or butyl rubber is particularly preferably used. By using these rubbers, a pressure-sensitive adhesive layer having excellent semiconductor chip retention at room temperature and excellent peelability can be formed. In addition, a pressure-sensitive adhesive layer having low affinity with sealing materials can be formed.
[0040] As the base polymer constituting the rubber-based adhesive, styrene-ethylene-propylene block copolymer (SEP) rubber, styrene-ethylene-butylene-styrene block copolymer (SEBS) rubber, styrene-isoprene-styrene block copolymer (SIS) rubber, styrene-butadiene-styrene block copolymer (SBS) rubber, and propylene rubber can also be preferably used. By using these rubbers, it is possible to form an adhesive layer that can exhibit high adhesion even in a high-temperature environment (for example, a high-temperature environment in processing such as when sealing a semiconductor chip). In the base polymer (rubber) having a styrene-derived structural unit, the content of the styrene-derived structural unit is preferably 15% by weight or more based on the total structural units in the base polymer.
[0041] The rubber-based pressure-sensitive adhesive may contain any suitable additives as necessary, such as crosslinking agents, vulcanizing agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, and antioxidants.
[0042] Any suitable tackifier is used as the tackifier contained in the rubber-based adhesive. For example, a tackifier resin is used as the tackifier. Specific examples of the tackifier resin include rosin-based tackifier resins, rosin derivative resins, petroleum-based resins, terpene-based resins, and ketone-based resins. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, based on 100 parts by weight of the base polymer.
[0043] Examples of the rosin resin contained in the rubber-based adhesive include gum rosin, wood rosin, and tall rosin. As the rosin resin, a stabilized rosin obtained by disproportionating or hydrogenating any suitable rosin may be used. In addition, as the rosin resin, a polymerized rosin, which is a multimer (typically a dimer) of any suitable rosin, or a modified rosin obtained by modifying any suitable rosin (for example, modification with an unsaturated acid) may be used.
[0044] Examples of the rosin derivative resin contained in the rubber-based pressure-sensitive adhesive include esters of the above-mentioned rosin-based resins, phenol-modified rosin-based resins, and esters of phenol-modified rosin-based resins.
[0045] Examples of the petroleum resin contained in the rubber-based adhesive include aliphatic petroleum resins, aromatic petroleum resins, copolymer petroleum resins, alicyclic petroleum resins, and hydrogenated versions of these.
[0046] Examples of the terpene resin contained in the rubber-based pressure-sensitive adhesive include α-pinene resin, β-pinene resin, aromatic modified terpene resin, and terpene phenol resin.
[0047] Examples of the ketone resin contained in the rubber-based adhesive include ketone resins obtained by condensing ketones (for example, aliphatic ketones, alicyclic ketones) with formaldehyde.
[0048] Examples of the crosslinking agent contained in the rubber-based adhesive include isocyanate-based crosslinking agents. Examples of the vulcanizing agent contained in the rubber-based adhesive include thiuram-based vulcanizing agents, quinoid-based vulcanizing agents, and quinone dioxime-based vulcanizing agents. By incorporating a crosslinking agent and / or a vulcanizing agent into the rubber-based adhesive, it is possible to form an adhesive layer that has high cohesiveness and is less likely to leave adhesive residue. The total content of the crosslinking agent and the vulcanizing agent is typically 0.1 to 20 parts by weight, more preferably 0.1 to 10 parts by weight, relative to 100 parts by weight of the base polymer.
[0049] In one embodiment, a rubber-based adhesive (Rub1) is used, which contains the above-mentioned base polymer (rubber), a hydroxyl-containing polyolefin, and a crosslinking agent a that can react with the hydroxyl group of the hydroxyl-containing polyolefin. In this rubber-based adhesive, the base polymer is not directly crosslinked, but the base polymer and the crosslinked hydroxyl-containing polyolefin are entangled, resulting in so-called pseudo-crosslinking. As a result, an adhesive layer that has high cohesiveness and is less likely to leave adhesive residue can be formed. The above-mentioned synthetic rubber is preferably used as the base polymer (rubber) used in this embodiment. In addition, an isocyanate-based crosslinking agent is preferably used as the crosslinking agent used in this embodiment.
[0050] The amount of the hydroxyl-containing polyolefin is preferably 0.5 parts by weight or more, more preferably 1.0 parts by weight or more, based on 100 parts by weight of the total of the base polymer (rubber), the hydroxyl-containing polyolefin, and the crosslinking agent a. If the amount is within this range, a pressure-sensitive adhesive layer with high cohesion can be formed. In addition, if the pressure-sensitive adhesive sheet has a base layer, the adhesiveness (anchor strength) between the base layer and the pressure-sensitive adhesive layer can be increased. In other words, if the amount of the hydroxyl-containing polyolefin is within the above range, a pressure-sensitive adhesive sheet with little adhesive residue can be obtained.
[0051] The amount of the crosslinking agent a is preferably 0.5 parts by weight or more, more preferably 1.0 parts by weight or more, based on 100 parts by weight of the total of the base polymer (rubber), the hydroxyl group-containing polyolefin, and the crosslinking agent a. If the amount is within this range, a pressure-sensitive adhesive layer with high cohesion can be formed. In addition, if the pressure-sensitive adhesive sheet has a base layer, the adhesiveness (anchor strength) between the base layer and the pressure-sensitive adhesive layer can be increased. In other words, if the amount of the crosslinking agent a is within the above range, a pressure-sensitive adhesive sheet with little adhesive residue can be obtained.
[0052] The hydroxyl group-containing polyolefin is preferably a resin having excellent compatibility with the synthetic rubber. Examples of the hydroxyl group-containing polyolefin include polyethylene polyols, polypropylene polyols, polybutadiene polyols, hydrogenated polybutadiene polyols, polyisoprene polyols, and hydrogenated polyisoprene polyols. Among them, hydrogenated polyisoprene polyols, polyisoprene polyols, and polybutadiene polyols are preferable from the viewpoint of compatibility with the synthetic rubber.
[0053] The number average molecular weight (Mn) of the hydroxyl group-containing polyolefin is preferably from 500 to 500,000, more preferably from 1,000 to 200,000, and further preferably from 1,200 to 150,000. The number average molecular weight can be measured in accordance with ASTM D2503.
[0054] The hydroxyl value (mgKOH / g) of the hydroxyl-containing polyolefin is preferably from 5 to 95, and more preferably from 10 to 80. The hydroxyl value can be measured in accordance with JIS K1557:1970.
[0055] (Silicone adhesive) As the silicone-based adhesive, any suitable adhesive may be used as long as the effect of the present invention can be obtained. As the silicone-based adhesive, for example, a silicone-based adhesive having a base polymer of silicone rubber or silicone resin containing organopolysiloxane is preferably used. As the base polymer constituting the silicone-based adhesive, a base polymer obtained by crosslinking the silicone rubber or silicone resin may be used. In this specification, "silicone rubber" means a polymer (for example, viscosity 1000 Pa·s) in which diorganosiloxane (D unit) as the main component is linked in a linear chain, and "silicone resin" means a polymer composed of triorganosylhemioxane (M unit) and silicate (Q unit) as the main components ("Material Design and Functionalization of Adhesives (Films and Tapes)", Technical Information Association, published on September 30, 2009).
[0056] The silicone rubber may be, for example, an organopolysiloxane containing dimethylsiloxane as a constituent unit. A functional group (for example, a vinyl group) may be introduced into the organopolysiloxane as necessary. The weight average molecular weight of the organopolysiloxane is preferably 100,000 to 1,000,000, and more preferably 150,000 to 500,000. The weight average molecular weight can be measured by GPC (solvent: THF).
[0057] The silicone resin is, for example, RSiO 1 / 2 Building block, SiO2 building block, RSiO 3 / 2 and R2SiO structural units (wherein R is a monovalent hydrocarbon group or a hydroxyl group).
[0058] The silicone rubber and silicone resin may be used in combination. The weight ratio of the silicone rubber to the silicone resin (rubber:resin) in the silicone pressure-sensitive adhesive is preferably 100:0 to 100:220, more preferably 100:0 to 100:180, and even more preferably 100:10 to 100:100. The silicone rubber and silicone resin may be contained in the silicone pressure-sensitive adhesive as a simple mixture, or the silicone rubber and silicone resin may be contained in the silicone pressure-sensitive adhesive in a partially condensed form. The rubber:resin ratio is determined by the composition of the silicone pressure-sensitive adhesive. 29 It can also be determined from the ratio of Q units (resin) to D units (rubber) measured by Si-NMR.
[0059] The silicone-based pressure-sensitive adhesive may contain any suitable additives as necessary, such as crosslinking agents, vulcanizing agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, and antioxidants.
[0060] Preferably, the silicone-based adhesive contains a crosslinking agent. Examples of the crosslinking agent include siloxane-based crosslinking agents and peroxide-based crosslinking agents. Any appropriate crosslinking agent can be used as the peroxide-based crosslinking agent. Examples of the peroxide-based crosslinking agent include benzoyl peroxide, t-butyl peroxybenzoate, dicumyl peroxite, and the like. Examples of the siloxane-based crosslinking agent include polyorganohydrogensiloxane, and the like. The polyorganohydrogensiloxane preferably has two or more hydrogen atoms bonded to a silicon atom. In addition, the polyorganohydrogensiloxane preferably has an alkyl group, a phenyl group, or a halogenated alkyl group as a functional group bonded to a silicon atom.
[0061] (Active energy ray curable adhesive) The pressure-sensitive adhesive may be an active energy ray curable pressure-sensitive adhesive that can be cured (high elastic modulus) by irradiation with active energy rays. By using an active energy ray curable pressure-sensitive adhesive, a pressure-sensitive adhesive sheet can be obtained that has low elasticity, high flexibility, and excellent handling properties when applied, and that can reduce adhesive strength by irradiating active energy rays when peeling is required. Examples of active energy rays include gamma rays, ultraviolet rays, visible light, infrared rays (heat rays), radio waves, alpha rays, beta rays, electron beams, plasma flow, ionizing rays, and particle beams. In this specification, the term "pressure-sensitive adhesive layer" simply refers to the pressure-sensitive adhesive layer before the pressure-sensitive adhesive is cured and its adhesive strength is reduced.
[0062] Examples of the resin material constituting the active energy ray-curable pressure-sensitive adhesive include those described in Ultraviolet Curing System (by Kiyomi Kato, published by General Technology Center, (1989)), Photocuring Technology (edited by Technical Information Association (2000)), JP 2003-292916 A, and Japanese Patent No. 4151850. More specifically, examples include a resin material (R1) containing a polymer as a base material and an active energy ray-reactive compound (monomer or oligomer), and a resin material (R2) containing an active energy ray-reactive polymer.
[0063] Examples of the polymer that is the base material include rubber-based polymers such as natural rubber, polyisobutylene rubber, styrene-butadiene rubber, styrene-isoprene-styrene block copolymer rubber, reclaimed rubber, butyl rubber, polyisobutylene rubber, and nitrile rubber (NBR); silicone-based polymers; and acrylic-based polymers. These polymers may be used alone or in combination of two or more. From the viewpoint of affinity with the sealing material, the polymers that are the base material may preferably be those exemplified as the base polymers of the acrylic adhesive, rubber adhesive, or silicone adhesive.
[0064] Examples of the active energy ray reactive compound include photoreactive monomers or oligomers having a functional group having a carbon-carbon multiple bond, such as an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, an acetylene group, etc. Specific examples of the photoreactive monomers or oligomers include (meth)acryloyl group-containing compounds such as trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; dimers to pentamers of the (meth)acryloyl group-containing compounds; and the like.
[0065] In addition, as the active energy ray reactive compound, a monomer such as epoxidized butadiene, glycidyl methacrylate, acrylamide, vinyl siloxane, or an oligomer composed of the monomer may be used. The resin material (R1) containing these compounds can be cured by high energy rays such as ultraviolet rays and electron beams.
[0066] Furthermore, the active energy ray reactive compound may be a mixture of an organic salt such as an onium salt and a compound having multiple heterocycles in the molecule. The organic salt of the mixture is cleaved by irradiation with active energy rays (e.g., ultraviolet rays, electron beams) to generate ions, which act as initiating species to cause a ring-opening reaction of the heterocycle to form a three-dimensional network structure. Examples of the organic salt include iodonium salts, phosphonium salts, antimonium salts, sulfonium salts, and borate salts. Examples of the heterocycle in the compound having multiple heterocycles in the molecule include oxirane, oxetane, oxolane, thiirane, and aziridine.
[0067] In the resin material (R1) containing the above-mentioned base polymer and the active energy ray reactive compound, the content of the active energy ray reactive compound is preferably 0.1 to 500 parts by weight, more preferably 1 to 300 parts by weight, and even more preferably 10 to 200 parts by weight, relative to 100 parts by weight of the base polymer. If the content is within such a range, a pressure-sensitive adhesive layer having low affinity with sealing materials can be formed.
[0068] The resin material (R1) containing the above-mentioned polymer as a base material and an active energy ray reactive compound may contain any appropriate additive as necessary. Examples of the additive include an active energy ray polymerization initiator, an active energy ray polymerization accelerator, a crosslinking agent, a plasticizer, a vulcanizing agent, and the like. As the active energy ray polymerization initiator, any appropriate initiator may be used depending on the type of active energy ray used. The active energy ray polymerization initiator may be used alone or in combination of two or more kinds. In the resin material (R1) containing the polymer as a base material and an active energy ray reactive compound, the content ratio of the active energy ray polymerization initiator is preferably 0.1 to 10 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the polymer as a base material.
[0069] Examples of the active energy ray reactive polymer include polymers having functional groups with carbon-carbon multiple bonds, such as acryloyl groups, methacryloyl groups, vinyl groups, allyl groups, and acetylene groups. Specific examples of polymers having active energy ray reactive functional groups include polymers composed of polyfunctional (meth)acrylates. The polymers composed of polyfunctional (meth)acrylates preferably have alkyl esters with 4 or more carbon atoms, more preferably have alkyl esters with 6 or more carbon atoms, even more preferably have alkyl esters with 8 or more carbon atoms, particularly preferably have alkyl esters with 8 to 20 carbon atoms, and most preferably have alkyl esters with 8 to 18 carbon atoms. If a polymer having a long side chain is used, a pressure-sensitive adhesive layer with low affinity to sealing materials can be formed. In the polymer, the content of the structural unit having an alkyl ester with 4 or more carbon atoms as a side chain is preferably 30% by weight or more, more preferably 50% by weight or more, even more preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight, based on the total structural units constituting the polymer. Within such a range, a pressure-sensitive adhesive layer having low affinity with the sealing material can be formed.
[0070] The resin material (R2) containing the active energy ray reactive polymer may further contain the active energy ray reactive compound (monomer or oligomer). The resin material (R2) containing the active energy ray reactive polymer may contain any appropriate additive as necessary. Specific examples of the additive are the same as those that may be contained in the resin material (R1) containing the polymer as a base material and the active energy ray reactive compound. In the resin material (R2) containing the active energy ray reactive polymer, the content ratio of the active energy ray polymerization initiator is preferably 0.1 to 10 parts by weight, more preferably 1 to 5 parts by weight, relative to 100 parts by weight of the active energy ray reactive polymer.
[0071] C. Base material Examples of the substrate include resin sheets, nonwoven fabrics, paper, metal foils, woven fabrics, rubber sheets, foam sheets, and laminates thereof (particularly laminates containing resin sheets). Examples of the resins constituting the resin sheets include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, ethylene-vinyl acetate copolymers (EVA), polyamides (nylons), wholly aromatic polyamides (aramids), polyimides (PI), polyvinyl chloride (PVC), polyphenylene sulfide (PPS), fluorine-based resins, and polyether ether ketones (PEEK). Examples of the nonwoven fabrics include nonwoven fabrics made of natural fibers having heat resistance, such as nonwoven fabrics containing Manila hemp; synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabrics, polyethylene resin nonwoven fabrics, and ester resin nonwoven fabrics. Examples of the metal foils include copper foils, stainless steel foils, and aluminum foils. Examples of the paper include Japanese paper and craft paper.
[0072] The thickness of the substrate can be set to any appropriate thickness depending on the desired strength or flexibility, the purpose of use, etc. The thickness of the substrate is preferably 1000 μm or less, more preferably 1 μm to 1000 μm, even more preferably 1 μm to 500 μm, particularly preferably 3 μm to 300 μm, and most preferably 5 μm to 250 μm.
[0073] The substrate may be subjected to a surface treatment, such as corona treatment, chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, ionizing radiation treatment, or coating with a primer.
[0074] Examples of the organic coating material include materials described in Plastic Hard Coat Materials II (CMC Publishing, (2004)). Preferably, a urethane-based polymer is used, more preferably polyacrylic urethane, polyester urethane, or a precursor thereof. This is because coating and application to a substrate is simple, and a wide variety of materials can be selected industrially and are inexpensively available. The urethane-based polymer is, for example, a polymer made of a reaction mixture of an isocyanate monomer and an alcoholic hydroxyl group-containing monomer (for example, a hydroxyl group-containing acrylic compound or a hydroxyl group-containing ester compound). The organic coating material may contain, as an optional additive, a chain extender such as polyamine, an antiaging agent, an oxidation stabilizer, and the like. The thickness of the organic coating layer is not particularly limited, but is, for example, suitable to be about 0.1 μm to 10 μm, preferably about 0.1 μm to 5 μm, and more preferably about 0.5 μm to 5 μm.
[0075] D. Second Adhesive Layer The second pressure-sensitive adhesive layer may be a pressure-sensitive adhesive layer composed of any appropriate pressure-sensitive adhesive. In one embodiment, as described above, the second pressure-sensitive adhesive layer further contains heat-expandable microspheres.
[0076] The adhesive contained in the second adhesive layer may be a curable adhesive (e.g., an active energy ray curable adhesive) or a pressure-sensitive adhesive. Examples of pressure-sensitive adhesives include acrylic adhesives and rubber adhesives. The adhesives described in Section B may be used as these adhesives.
[0077] The heat-expandable microspheres may be any suitable type of heat-expandable microspheres, so long as they are capable of expanding or foaming upon heating. For example, the heat-expandable microspheres may be microspheres having a substance that easily expands upon heating encapsulated in an elastic shell. Such heat-expandable microspheres may be produced by any suitable method, such as a coacervation method or an interfacial polymerization method.
[0078] Examples of substances that easily expand when heated include low-boiling liquids such as propane, propylene, butene, normal butane, isobutane, isopentane, neopentane, normal pentane, normal hexane, isohexane, heptane, octane, petroleum ether, methane halides, and tetraalkylsilanes; azodicarbonamide that gasifies by thermal decomposition; and the like.
[0079] Examples of materials constituting the shell include polymers composed of nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaronitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; and amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide. Polymers composed of these monomers may be homopolymers or copolymers. Examples of such copolymers include vinylidene chloride-methyl methacrylate-acrylonitrile copolymer, methyl methacrylate-acrylonitrile-methacrylonitrile copolymer, methyl methacrylate-acrylonitrile copolymer, acrylonitrile-methacrylonitrile-itaconic acid copolymer, and the like.
[0080] The heat-expandable microspheres may be made of an inorganic or organic foaming agent, such as ammonium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and various azides. Examples of organic foaming agents include fluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide and barium azodicarboxylate; hydrazine compounds such as paratoluenesulfonylhydrazide, diphenylsulfone-3,3'-disulfonylhydrazide, 4,4'-oxybis(benzenesulfonylhydrazide) and allylbis(sulfonylhydrazide); semicarbazide compounds such as p-toluylenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholyl-1,2,3,4-thiatriazole; and N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide.
[0081] The heat-expandable microspheres may be commercially available products. Specific examples of commercially available heat-expandable microspheres include "Matsumoto Microsphere" (product name: F-30, F-30D, F-36D, F-36LV, F-50, F-50D, F-65, F-65D, FN-100SS, FN-100SSD, FN-180SS, FN-180SSD, F-190D, F-260D, F-2800D) manufactured by Matsumoto Yushi Seiyaku Co., Ltd., and "Expancel" (product name: 053 -40, 031-40, 920-40, 909-80, 930-120), "Dieform" manufactured by Kureha Chemical Industry Co., Ltd. (grades: H750, H850, H1100, S2320D, S2640D, M330, M430, M520), and "Advancell" manufactured by Sekisui Chemical Co., Ltd. (grades: EML101, EMH204, EHM301, EHM302, EHM303, EM304, EHM401, EM403, EM501).
[0082] The particle size of the heat-expandable microspheres before heating is preferably 0.5 μm to 80 μm, more preferably 5 μm to 45 μm, further preferably 10 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Thus, the particle size of the heat-expandable microspheres before heating, expressed in terms of average particle size, is preferably 6 μm to 45 μm, more preferably 15 μm to 35 μm. The particle size and average particle size are values determined by a particle size distribution measurement method using a laser scattering method.
[0083] The heat-expandable microspheres preferably have an appropriate strength so that they do not burst until their volumetric expansion rate reaches at least 5 times, more preferably at least 7 times, and even more preferably at least 10 times. When such heat-expandable microspheres are used, their adhesive strength can be efficiently reduced by heat treatment.
[0084] The content of the heat-expandable microspheres in the pressure-sensitive adhesive layer can be appropriately set depending on the desired decrease in adhesive strength, etc. The content of the heat-expandable microspheres is, for example, 1 to 150 parts by weight, preferably 10 to 130 parts by weight, and more preferably 25 to 100 parts by weight, relative to 100 parts by weight of the base polymer forming the second pressure-sensitive adhesive layer.
[0085] When the pressure-sensitive adhesive layer contains heat-expandable microspheres, the arithmetic surface roughness Ra of the pressure-sensitive adhesive layer before the heat-expandable microspheres expand (i.e., before heating) is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. Within such a range, a pressure-sensitive adhesive sheet having excellent adhesion to an adherend can be obtained. Such a pressure-sensitive adhesive layer having excellent surface smoothness can be obtained, for example, by setting the thickness of the pressure-sensitive adhesive layer within the above range, or, in the case of comprising another pressure-sensitive adhesive layer, by applying the pressure-sensitive adhesive layer to a separator and transferring it. As explained in the above section A, when the pressure-sensitive adhesive sheet of the present invention further comprises another pressure-sensitive adhesive layer, the other pressure-sensitive adhesive layer may contain heat-expandable microspheres. Even when the other pressure-sensitive adhesive layer contains heat-expandable microspheres, the arithmetic surface roughness Ra of the pressure-sensitive adhesive layer is preferably within the above range.
[0086] When the pressure-sensitive adhesive layer contains heat-expandable microspheres, the pressure-sensitive adhesive layer preferably contains a pressure-sensitive adhesive composed of a base polymer having a dynamic storage modulus at 80°C in the range of 5 kPa to 1 MPa (more preferably 10 kPa to 0.8 MPa). Such a pressure-sensitive adhesive layer can form a pressure-sensitive adhesive sheet that has appropriate adhesion before heating and is prone to lose adhesive strength upon heating. The dynamic storage modulus can be measured using a dynamic viscoelasticity measuring device (for example, "ARES" manufactured by Rheometrics Corporation) under measurement conditions of a frequency of 1 Hz and a heating rate of 10°C / min.
[0087] E. Manufacturing method of adhesive sheet The pressure-sensitive adhesive sheet of the present invention can be produced by any suitable method. For example, the pressure-sensitive adhesive sheet of the present invention can be produced by a method of directly coating a composition containing a pressure-sensitive adhesive on a substrate, or a method of coating a composition containing a pressure-sensitive adhesive on any suitable substrate and transferring the formed coating layer to the substrate. The composition containing a pressure-sensitive adhesive can contain any suitable solvent.
[0088] When forming a pressure-sensitive adhesive layer containing heat-expandable microspheres, the pressure-sensitive adhesive layer can be formed by coating a substrate with a composition containing heat-expandable microspheres, a pressure-sensitive adhesive, and any suitable solvent. Alternatively, the pressure-sensitive adhesive layer containing heat-expandable microspheres can be formed by sprinkling heat-expandable microspheres on a pressure-sensitive adhesive coating layer and then embedding the heat-expandable microspheres in the pressure-sensitive adhesive using a laminator or the like.
[0089] Any suitable coating method can be adopted as the coating method of the pressure sensitive adhesive and each composition. For example, each layer can be formed by drying after coating. For example, the coating method can be a coating method using a multi-coater, a die coater, a gravure coater, an applicator, etc. For example, the drying method can be natural drying, heat drying, etc. The heating temperature when heat drying can be set to any suitable temperature according to the characteristics of the material to be dried. EXAMPLES
[0090] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0091] (1) SP value The sp value of the polymer in the adhesive layer after the adhesive sheet was formed was calculated by the Fedors method (Hideki Yamamoto, "sp Value: Fundamentals, Applications and Calculation Methods", Johokki Publishing Co., Ltd., published April 3, 2006, pp. 66-67). Specifically, the sp value is calculated by dividing the evaporation energy Δe (cal) of each atom or atomic group forming the polymer at 25° C. by the molar volume ΔV (cm) of each atom or atomic group forming the polymer at 25° C. 3 ) was calculated using the following formula: Sp value = (ΣΔe / ΣΔv) 1 / 2 Furthermore, when the polymer is a copolymer, the SP value is calculated by calculating the SP value of each homopolymer of each structural unit constituting the copolymer, and then multiplying each of these SP values by the molar fraction of each structural unit and adding up the results. In the above case, the method of analyzing each constituent unit (polymer composition analysis) can be performed by appropriately collecting only the adhesive layer from the adhesive sheet, immersing it in an organic solvent such as dimethylformamide (DMF), acetone, methanol, or tetrahydrofuran (THF), recovering the solvent-soluble portion, and determining the composition by gel permeation chromatography (GPC), nuclear magnetic resonance spectroscopy (NMR), infrared spectroscopy (IR), or mass spectrometry. (2) Contact angle The adhesive sheet was placed on a slide glass with the adhesive layer facing up, and the contact angle of the adhesive layer surface with 4-tert-butylphenyl glycidyl ether was measured. 2 μl of 4-tertiary butylphenyl glycidyl ether was dropped onto the surface of the adhesive layer, and the contact angle was measured after 5 seconds (N=5). The contact angle was measured using a contact angle meter (manufactured by Kyowa Interface Co., Ltd., product name "CX-A type") in an atmosphere of 23°C and 50% RH. (3) Adhesion to sealing resin (adhesion to epoxy resin at 23°C when the epoxy resin is cured on the adhesive layer) A 0.6 mmt picture frame-shaped spacer (inner dimensions 100 mm x 100 mm) was placed on the surface of the adhesive layer of the adhesive sheet (size: 125 mm x 125 mm) obtained in the Examples and Comparative Examples, and granular epoxy sealing resin (G730 manufactured by Sumitomo Bakelite Co., Ltd.) was sprayed inside the spacer so that the resin thickness after curing would be 0.6 mmt. A silicone-treated release liner was then placed on top, and the evaluation sample was compression molded at 150°C for 600 seconds at 0.3 MPa using a vacuum compression molding machine, and then heated at 150°C for 1 hour to cure, forming a sealing resin on the adhesive sheet of the adhesive sheet, thereby forming a structure. The structure obtained as described above was cooled, and then a sample (width 20 mm × length 100 mm) was cut out from the structure, and the adhesive sheet was peeled off from the sample using a tensile tester. After setting the sample in the tensile tester, it was left for 30 minutes at an environmental temperature of 23 ° C (room temperature). The test force when the tape was then peeled off at room temperature (300 mm / min 180 degree peel) was taken as the sealing resin adhesion strength. (4) Shear adhesive strength The adhesive sheet (size: 20 mm x 20 mm) obtained in the examples and comparative examples was attached and fixed on a predetermined base (e.g., a 20 mm x 20 mm silicon chip) using double-sided tape No. 585 manufactured by Nitto Denko Corporation on the side opposite to the adhesive layer, and a 5 mm x 5 mm silicon chip (mirror surface) was attached vertically to the adhesive layer surface of the adhesive sheet using tweezers so that the chip corners do not touch the adhesive surface layer. After that, the silicon chip was heated at 130°C for 30 minutes to be attached to the adhesive surface, and an evaluation sample was prepared. For the evaluation sample, a Nordson dage4000 was used at an ambient temperature of 150°C, with measurement terminals set on the side of a 5 mm x 5 mm silicon chip at a height of 250 μm from the attachment surface, and an external force was applied horizontally to the chip at a shear rate of 500 μm / sec. The maximum fracture load was read from the load-displacement curve obtained, and this was taken as the shear adhesion strength at an ambient temperature of 150°C. (5) Cross-sectional observation of sealing resin A glass filler-containing granular sealing resin (G730 manufactured by Sumitomo Bakelite Co., Ltd.) was sprayed onto the surface of the adhesive layer of the adhesive sheets obtained in the Examples and Comparative Examples, and pressure was applied under the conditions of 145°C x 10 min x 0.3 MPa to form a resin layer. After heating at 150°C x 4 h, the temperature was returned to room temperature, and the tape was peeled off at room temperature (300 mm / min 180 degree peel). Next, the part where the adhesive tape was attached to the resin was cut, and the cross section was sputtered with Pt / Pd alloy, and then observed with a SEM (Hitachi "S-3400N", applied voltage 10 kV, high vacuum, SE mode, 1000x). A sample in which a layer not containing a glass filler (a pressure-sensitive adhesive layer or a mixed phase containing pressure-sensitive adhesive layer components and resin layer components) was observed on a resin layer containing a glass filler was marked with an ◯, and a sample in which no layer was formed was marked with an X.
[0092] [Example 1] A composition for forming an adhesive layer was prepared by mixing 100 parts by weight of acrylic copolymer A (a copolymer of butyl acrylate (BA), methyl methacrylate (MMA), and hydroxyethyl acrylate (HEA), BA:MMA:HEA = 65:30:5 (weight ratio)), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), and 0.01 parts by weight of a reaction aid (manufactured by Tokyo Fine Chemical Co., Ltd., product name "OM-5"). The composition for forming an adhesive layer was applied to one side of a polytetrafluoroethylene film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness 38 μm) as a substrate to obtain an adhesive sheet composed of the substrate and an adhesive layer (thickness 5 μm). The obtained pressure-sensitive adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0093] [Example 2] An adhesive sheet was obtained in the same manner as in Example 1, except that a composition for forming an adhesive layer was prepared without adding a reaction aid and by further blending 10 parts by weight of a terpene phenol-based tackifier resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "SUMILITE RESIN PR51732") The adhesive sheet obtained was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0094] [Example 3] An adhesive layer-forming composition was prepared by further blending 20 parts by weight of a terpene phenol-based tackifier resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar S145") without adding a reaction aid, and an adhesive sheet was obtained in the same manner as in Example 1, except that the thickness of the adhesive layer was 10 μm. The obtained adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0095] [Example 4] An adhesive layer-forming composition was prepared by further blending 20 parts by weight of a terpene phenol-based tackifier resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar T145") without adding a reaction aid, and an adhesive sheet was obtained in the same manner as in Example 1, except that the thickness of the adhesive layer was 10 μm. The obtained adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0096] [Example 5] A composition for forming an adhesive layer was prepared by mixing 100 parts by weight of acrylic copolymer B (a copolymer of 2-ethylhexyl acrylate (2EHA), butyl acrylate (BA), acrylic acid (AA), and hydroxyethyl acrylate (HEA), 2EHA:BA:AA:HEA=50:50:4:1 (weight ratio)), 5 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), and 20 parts by weight of a terpene phenol tackifying resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "Sumilite Resin PR12603"). The composition for forming an adhesive layer was applied to one side of a polytetrafluoroethylene film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness 38 μm) as a substrate to obtain an adhesive sheet composed of the substrate and an adhesive layer (thickness 10 μm). The obtained pressure-sensitive adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0097] [Example 6] A composition for forming an adhesive layer was prepared by mixing 100 parts by weight of acrylic copolymer C (a copolymer of 2-ethylhexyl acrylate (2EHA), ethyl acrylate (EA), methyl methacrylate (MMA), and hydroxyethyl acrylate (HEA), 2EHA:EA:MMA:HEA=30:65:5:5 (weight ratio)), 0.05 parts by weight of a reaction aid (manufactured by Tokyo Fine Chemical Co., Ltd., product name "OL-1"), 3 parts by weight of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), and 20 parts by weight of a rosin-based tackifier (manufactured by Arakawa Chemical Industries Co., Ltd., product name "Pensel D125"). The composition for forming an adhesive layer was applied to one side of a polytetrafluoroethylene film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness 38 μm) as a substrate to obtain an adhesive sheet composed of the substrate and an adhesive layer (thickness 10 μm). The obtained pressure-sensitive adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0098] [Comparative Example 1] A composition for forming an adhesive layer was prepared by mixing 100 parts by weight of acrylic copolymer D (a copolymer of 2-ethylhexyl acrylate (2EHA) and hydroxyethyl acrylate (HEA), 2EHA:HEA = 100:5 (weight ratio)), 0.05 parts by weight of a reaction aid (manufactured by Tokyo Fine Chemical Co., Ltd., product name "OL-1"), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), and 10 parts by weight of a terpene phenol-based tackifying resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "Sumilite Resin PR12603"). The composition for forming an adhesive layer was applied to one side of a polytetrafluoroethylene film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness 38 μm) as a substrate to obtain an adhesive sheet composed of the substrate and an adhesive layer (thickness 10 μm). The obtained pressure-sensitive adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0099] [Comparative Example 2] A composition for forming an adhesive layer was prepared by mixing 100 parts by weight of acrylic copolymer E (a copolymer of 2-ethylhexyl acrylate (2EHA) and acrylic acid (AA), 2EHA:AA = 100:5 (weight ratio)), 0.5 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), and 10 parts by weight of a terpene phenol tackifying resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar S145"). The composition for forming an adhesive layer was applied to one side of a polytetrafluoroethylene film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness 38 μm) as a substrate to obtain an adhesive sheet composed of the substrate and an adhesive layer (thickness 10 μm). The obtained pressure-sensitive adhesive sheet was subjected to the above evaluations (1) to (4). The results are shown in Table 1.
[0100] [Table 1]
[0101] For Example 1 and Comparative Example 1, SEM photographs of the observed surface in "(5) Cross-sectional observation of sealing resin" are shown in FIG. 3. In the cross-sectional sample created from the Example, a resin layer containing a gray glass filler and a darker gray layer not containing glass filler (i.e., a pressure-sensitive adhesive layer containing a mixed layer) were observed, whereas in the Comparative Example, only a resin layer containing a gray glass filler was observed. The results of Examples 2 to 6 were similar to those of Example 1. Furthermore, the results of Comparative Example 2 were similar to those of Comparative Example 1. [Explanation of symbols]
[0102] 10 Base material 20 Adhesive layer 30 Second adhesive layer 100, 200 Adhesive Sheet
Claims
1. A substrate and a pressure-sensitive adhesive layer disposed on at least one side of the substrate, The pressure-sensitive adhesive layer contains a pressure-sensitive adhesive, the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive, the acrylic pressure-sensitive adhesive comprises, as a base polymer, an acrylic polymer having an alkyl ester having 6 or less carbon atoms as a side chain; the content of the structural unit having an alkyl ester having 6 or less carbon atoms as a side chain is 50% by weight or more relative to all structural units constituting the acrylic polymer, The base polymer has an Sp value of 19.5 (J / cm 3 ) 1/2 ~25 (J / cm 3 ) 1/2 and the shear adhesive strength at 150°C when the pressure-sensitive adhesive layer is attached to a silicon chip is 400 g or more; the contact angle of the pressure-sensitive adhesive layer to 4-tertiary butyl phenyl glycidyl ether is 47° or less; An adhesive sheet used for resin sealing with epoxy resin.
2. 2. The adhesive sheet used for resin sealing with an epoxy resin according to claim 1, comprising: the substrate; the adhesive layer disposed on one side of the substrate; and a second adhesive layer disposed on the opposite side of the substrate to the adhesive layer.
Citation Information
Patent Citations
Chip-shaped electronic component and its manufacturing method, and pseudo wafer used for manufacturing method of chip-shaped electronic component and its manufacturing method
JP2001308116A
Chip-shaped electronic component and its manufacturing method, and pseudo-wafer used for manufacture of chip- shaped electronic component and its manufacturing method
JP2001313350A
Method of sticking pressure-sensitive adhesive sheet onto vehicle coating film surface
JP2008274153A
Pressure sensitive adhesive sheet
JP2015168711A
Adhesive sheet
JP2018193563A
